(untitled) (Global Journal of Science Frontier Research, 2014)
A new measure, called average code word length of order and type has been defined and its relationship with a result of Tuteja and Bhaker ’useful’ inaccuracy measure has been discussed. Using , some noiseless coding theorems for discrete noiseless channel has been proved. The results obtained in this paper generalizes some well known results available in the literature.